120k views
3 votes
How do I do


\sqrt{9 - n = \sqrt{ (n)/(2) } }
I need to find the value of n​

User Roman Unt
by
5.1k points

1 Answer

5 votes

I'm assuming that there's a typo and you mean


√(9-n) = \sqrt{(n)/(2)}

We must use two key facts: the square root is defined only for non-negative inputs, so we must require


\begin{cases}9-n\geq 0\\(n)/(2)\geq 0\end{cases} \iff \begin{cases}n\leq 9\\n\geq 0\end{cases}

So, we will only accept values in the range


0 \leq n \leq 9

Secondly, where defined, the square root is an injective function. This means that you can only have two equal outputs if you start from two equal inputs:


√(x)=√(y)\iff x=y

So, in your case, we have


√(9-n) = \sqrt{(n)/(2)} \iff 9-n = (n)/(2)

Adding n to both sides gives


9 = (3n)/(2) \iff 3n = 18 \iff n = 6

User Dsteplight
by
5.3k points